Adaptasi terhadap Dampak Iklim Ekstrem pada Pola Tanam Jeruk Siam Banjar (Citrus suhuensis) dengan Sistem Surjan - Gusti Rusmayadi; Umi Salawati; Dewi Erika Adriani (Institut Pertanian Bogor, 2022)
Climate change has a real impact on yields, seasonal shifts, cropping patterns of citrus siam banjar plantations (Citrus suhuensis) on tidal land. This research aims to analyze the relationship of the cropping patterns of surjan systems and climate extremes, as an effort to overcome climate change. The research was conducted in Batola in 2020 using written and oral survey methods. Data was extracted from farmers and related institutions. The respondents consisted of 45 men and 45 women. On each sub-district, 2 villages were surveyed according to tidal land type, namely Marabahan district (SP1 and SP2) type C, Mandastana subdistrict (Karang Indah and Karang Bunga) type B, and Cerbon district (Simpang Nungki and Kambat River) type A. The results showed that the chance of El-Niño was around 16.7-22.7%, while La-Niña reached 40%. The total extreme event was 67.8% of La-Niña side by side with El-Niño 15 times and generally El-Niño precedes La-Niña by about 40%. The total extreme event reached 62.7%. The productivity of citrus observations in 2015-2019 was 1.274 ton/ha and during El-Niño yields decreased by 0.05 ton/ha. Crops damaged by El-Niño in 20152016 were -2% of the area of 6,825.03 ha. More than 90% of farmers during extreme events applied a pattern of superior local-rice oranges-rice to tabukan and oranges-vegetables on mounds. Cropping patterns on tidal tidal land show a high level of resistance to climate change because they have not changed much for decades in both normal, dry, and wet climatic conditions. Keywords: El-Niño, extreme climate, La-Niña, siam banjar oranges, tidal land type A, B dan C